2010
DOI: 10.1007/s10544-010-9473-7
|View full text |Cite
|
Sign up to set email alerts
|

Modulating malignant epithelial tumor cell adhesion, migration and mechanics with nanorod surfaces

Abstract: The failure of tumor stents used for palliative therapy is due in part to the adhesion of tumor cells to the stent surface. It is therefore desirable to develop approaches to weaken the adhesion of malignant tumor cells to surfaces. We have previously developed SiO₂ coated nanorods that resist the adhesion of normal endothelial cells and fibroblasts. The adhesion mechanisms in malignant tumor cells are significantly altered from normal cells; therefore, it is unclear if nanorods can similarly resist tumor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Tumor formation involves cell adhesions and interaction with surrounding cells and extracellular matrix [24]. Abnormal adhesion may be a determinant of epithelial tumor formation [25,26]. Thus, we observed the effect of adhesion molecule NCAM1 on the biological behavior of AB.…”
Section: Discussionmentioning
confidence: 72%
“…Tumor formation involves cell adhesions and interaction with surrounding cells and extracellular matrix [24]. Abnormal adhesion may be a determinant of epithelial tumor formation [25,26]. Thus, we observed the effect of adhesion molecule NCAM1 on the biological behavior of AB.…”
Section: Discussionmentioning
confidence: 72%
“…The nanotips generated in this work were also the first recorded instance of this particular morphology of Na 2 O. In addition to nanotips negatively affecting cell adhesion or hydrophobicity [4,31,[34][35][36], research has shown that increasing the sodium oxide content in bioactive glass can reduce cell proliferation [54]. Thus it was hypothesized that the networked SiO 2 nanofiber structures would act as an aECM aiding in cell growth, while surfaces with Na 2 O nanotip structures would be detrimental to cells.…”
Section: Introductionmentioning
confidence: 76%
“…Furthermore, nanorod and nanotip structures on surfaces have been shown to impair cell adhesion [4,31,[34][35][36]. Complications with this explanation arise when consideration is given to the reactivity of Na 2 O in aqueous media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell mechanics is already well-represented in chemical engineering departments across the country, including faculty members who are either chemical engineers by training or hold appointments in chemical engineering departments. Active areas of interest that are benefiting from chemical engineering thinking include cell migration, ,, actin and microtubule assembly and mechanics, , adhesion bonds and traction forces, ,, cell–cell adhesion, neutrophil rolling, , cell behavior under flows, , ligand–receptor interactions, , tissue mechanics, ,, nuclear mechanics, and cell mechanotransduction. Cell mechanics will continue to remain an important and vibrant part of the chemical engineering profession for many years to come.…”
Section: Discussionmentioning
confidence: 99%